2010
DOI: 10.1182/blood-2010-02-270918
|View full text |Cite
|
Sign up to set email alerts
|

A role for factor XIIa–mediated factor XI activation in thrombus formation in vivo

Abstract: Mice lacking factor XII (fXII) or factor XI (fXI) are resistant to experimentallyinduced thrombosis, suggesting fXIIa activation of fXI contributes to thrombus formation in vivo. It is not clear whether this reaction has relevance for thrombosis in primates. In 2 carotid artery injury models (FeCl 3 and Rose Bengal/laser), fXII-deficient mice are more resistant to thrombosis than fXI-or factor IX (fIX)-deficient mice, raising the possibility that fXII and fXI function in distinct pathways. Antibody 14E11 binds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
303
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(321 citation statements)
references
References 49 publications
12
303
2
4
Order By: Relevance
“…However, thrombus formation in FXII −/− mice is defective in venous stasis models, arterial thrombosis and stroke models, and models for PE. [23][24][25][26] Therefore, FXII may become a target for safe anticoagulation with thromboprotective but sustained hemostatic properties. FXII seems to be important for thrombus stability.…”
Section: The Vessel Wall and Coagulationmentioning
confidence: 99%
“…However, thrombus formation in FXII −/− mice is defective in venous stasis models, arterial thrombosis and stroke models, and models for PE. [23][24][25][26] Therefore, FXII may become a target for safe anticoagulation with thromboprotective but sustained hemostatic properties. FXII seems to be important for thrombus stability.…”
Section: The Vessel Wall and Coagulationmentioning
confidence: 99%
“…[22][23][24][25][26] For example, inhibitory factor XI antibodies, which prevent the activation of factor XI by factor XII, protected mice from ferric chloride-induced arterial and venous thrombosis. 27,28 Furthermore, factor XI and factor XI antisense oligonucleotides have been studied in higher species using a vascular graft occlusion model in primates, 29,30 which paved the way for human studies using factor XI antisense oligonucleotides. Human data from patients undergoing total knee replacement surgery are expected this year.…”
Section: Factor XImentioning
confidence: 99%
“…In recent years, however, it has been shown that FXII −/− mice are resistant to experimentally induced thrombosis34, 35 and ischemic brain injury 19. As deficiency of FXII is not associated with abnormal hemorrhaging from injury sites (hemostasis) either in patients or in animals,19, 34 inhibition of activated FXII prevented arterial thrombosis and ischemic brain injury20, 36 without affecting hemostasis 20, 37.…”
Section: Discussionmentioning
confidence: 99%